2021
DOI: 10.1111/ijfs.15017
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic and extrusion pretreatments of defatted rice bran to improve functional properties of protein concentrates

Abstract: Summary This study evaluated effects of enzymatic, extrusion and combined pretreatments on functional and thermal properties of protein concentrates from defatted rice bran to improve their applicability to food formulations. After the pretreatments, protein concentrates were recovered by alkaline solubilisation and isoelectric point precipitation. Water absorption capacity, oil absorption capacity, emulsifying and foaming properties, and thermal stability were determined in protein concentrates. Yields of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Protein concentrates obtained aer extrusion of DRB improved functionality, making them suitable for food formulations. 55 Raman spectroscopy showed an increase in unordered structure and a decrease in the a-helix and b-sheet structures of RBP during extrusion, depending on the extrusion temperature. This inuenced tyrosine and tryptophan content and protein polarity.…”
Section: Application Of the Extruded Rb In Different Food Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein concentrates obtained aer extrusion of DRB improved functionality, making them suitable for food formulations. 55 Raman spectroscopy showed an increase in unordered structure and a decrease in the a-helix and b-sheet structures of RBP during extrusion, depending on the extrusion temperature. This inuenced tyrosine and tryptophan content and protein polarity.…”
Section: Application Of the Extruded Rb In Different Food Productsmentioning
confidence: 99%
“…49 Moreover, a protein concentrate derived from extruded DRB exhibits elevated oil absorption capacity, emulsifying activity index and foaming capacity compared to enzymatic hydrolysis. 55 The increased pressure during extrusion alters protein arrangement, enhancing water absorption capacity and foaming potential. 56 When comparing different extrusion treatments, extruded RB followed by micronization shows superior WSI, whiteness, nutrient release and decreased WBC and swelling capacity compared to radio frequency-treated RB followed by micronization.…”
Section: Effect Of Extrusion On the Physical And Nutritional Qualitiesmentioning
confidence: 99%
“…Currently, proteins can be hydrolyzed by biotechnological methods such as enzymatic, fermentative, or germination. In addition, physical processes such as thermoplastic extrusion (Leal et al, 2021;Ma et al, 2018), hydrothermal treatment (Liang et al, 2020), and ultrasound (Hayta et al, 2020) has been applied as a pretreatment to favor the enzymatic action due to the denaturation of the quaternary and tertiary structures of vegetable proteins, favoring hydrodynamic (gelling) and surfactant (emulsification and aeration) properties (Mozafarpour et al, 2019;Santos et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Osborne classification has been used to separate high‐purity components of many legume proteins (Sun et al ., 2021). Many studies have shown that proteins are assisted extracted by ultrasound treatment, microwave treatment, high‐pressure treatment, and enzymatic degradation (Amagliani et al ., 2017; Wen et al ., 2018; Leal et al ., 2021). The functional properties of proteins are greatly influenced not only by raw materials (e.g., variety) but also by processing parameters and/or extraction methods (Yao et al ., 2021; Yu et al ., 2021a,b).…”
Section: Introductionmentioning
confidence: 99%